Pencegahan Stunting Melalui Implementasi Program Pemberdayaan dan Kesejahteraan Keluarga di Desa Lalapin Kabupaten Kotabaru - Saifudin, Saifudin; Rahman, Gazali; Agustina, Sitha Elvia (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
This article aims to analyze stunting prevention through the implementation of the Family Empowerment and Welfare Program in Kotabaru Regency by taking a sample of research locations in Lalapin Village. The research results show that the indicators for implementing stunting prevention are appropriate in the context of implementing the Family Empowerment and Welfare Program. Several main indicators such as suitability of public policy implementation, interests of target groups, types of benefits, degree of change, location of decision making, program implementation, involvement of resources, power, interests, strategies of actors involved, as well as community compliance and understanding are implemented to prevent stunting. Based on research results, preventing stunting through the implementation of the Family Empowerment and Welfare Program has had a positive influence on the village. The actor's strategy is to provide outreach, counseling, and training about the bad impacts of stunting and appropriate ways to prevent it. However, in its implementation, several obstacles and problems were still found, such as village community compliance and understanding not yet fully occurring because they did not comply with the routine posyandu schedule. In general, prevention of stunting through the Family Empowerment and Welfare Program in Lalapin Village, Kotabaru Regency has been implemented well.